Healthy Lifestyle as Necessary Factor of Strengthening Competitive Positions and Increasing of Effective Management used at the Enterprises of the Service Industry - SOZINOVA, Anastasia Andreevna; PUGACH, Valentin Nikolaevich; GANGHEEVA, Svetlana Gennadevna (Journal of Advanced Research in Law and Economics, 2017)
The article analyzes the possibility of connecting a healthy lifestyle with workday. It shows that the presence of health management in the company has a positive effect on efficiency working and is an important part of corporate culture, which makes the company more competitive among others one. According to the fact that competitiveness is one of the important factors of effective activities for every company, the subject of research is relevant. Traditional ways for increasing the competitiveness of a company through such factors as price and quality of the items are available to all businessmen. That is why nonstandard ways and decisions in the field of management of the company are more attractive for all companies of all types of activities. The results of research which is included into the article are: necessity of forming competitive human capital; modification of top-managers’; outlook of the companies which are connected in activities with the human capital and elaboration of a new model with using modern techniques of using human resources by companies of Service Industry Also health management of a staff as a factor of increasing of competitiveness must strengthen the competitive position of any company.